AN ERROR ANALYSIS OF USING CONJUNCTION IN THE THESIS ABSTRACTS MECHANICAL ENGINEERING STUDENTS’ UNIVERSITY OF PASIR PENGARAIAN - Rahayu, Pipit; Eripuddin; Permata Sari, Intan; Nurazima Juhastri, Azi (English Study Program University of Pasir Pengaraian, 2024)
This research is about the errors analysis of using conjunctions in the thesis abstracts of mechanical engineering students at Pasir Pengaraian University. The purpose of this research is to find out whether there are four types of conjunction usage errors in the thesis abstracts of mechanical engineering students at Pasir Pengaraian University. This research was conducted using descriptive qualitative research. This research was conducted at Pasir Pengaraian University, with the research focus being mechanical engineering students there. The data was collected from 36 abstract data sets of mechanical engineering students. The results showed that there were errors in the use of conjunctions in the thesis abstracts of mechanical engineering student’s class of 2020-2023. In the abstracts of mechanical engineering students, there are three types of conjunction usage errors, namely (addition) extra conjunctions not needed in the abstract. Secondly (omission) the omission of conjunctions that are needed in the sentence in the abstract. Third (misformation) incorrect conjunctions used in the abstract. From the three types, the most dominant error is omission.